الزاوية الصديقية وأثرها في الحركة الحديثية في القرن الرابع عشر: دراسة وصفية = The Siddiqi Zawiya and its impact on the Hadith movement in the 14th century: a descriptive study - Gasmelsid, Saadeldin Mansour; Mohamad Akbar, Tariq Jaffri (International Islamic University Malaysia, 2025)
This research aims to highlight the role of prominent figures of the Siddiqiyya al-Ghumari Sufi order in revitalizing the Hadith movement in our contemporary era. It is a descriptive study aimed at introducing Sufi orders in general and their role in jihad, then specifically discussing the Siddiqiyya order in terms of its history, ideology, activities, and the significance of its figures in the Prophetic tradition. The researchers outline the methodological aspects of these figures' efforts in the Hadith movement. The researchers conclude that the luminaries of the Siddiqiyya order are among the most significant scholarly families contributing to the contemporary Hadith movement.